China's Cyberwarriors. - Bishop, Mac William (Foreign Policy)
A recent series of cyber attacks aimed at Taiwan and the United States may confirm cyber-security experts' fears that giving the Chinese government access to the source code of its Windows operating system would make it easier for China's People's Liberation Army (PLA) to employ new information-warfare techniques. There has been a noticeable increase in information-warfare attacks in the past few months. The PLA has been especially effective in developing a cohort of young hackers, and the recent attacks seem to be part of a Chinese plan to exploit a continuing political crisis and a series of government corruption scandals in Taiwan.